2009
DOI: 10.1097/hjr.0b013e32832a4e3b
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of statins after percutaneous coronary intervention

Abstract: Background Evidence about the efficacy of statin treatment among patients after percutaneous coronary intervention (PCI) is very limited. The rapid advancement in PCI technology and near universal use of adjunctive cardioprotective medications make it necessary to formally assess the effect of statin therapy on cardiac events after PCI. Design This was a multicenter prospective cohort study Methods Patients who received stent implantation and survived to hospital discharge from the National Heart, Lung, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
0
8
0
3
Order By: Relevance
“…Recent studies have shown that the presence of CKD is an independent predictor of subsequent CVD events and mortality in patients with a history of myocardial infarction [19,20,21], acute coronary syndromes [22] and revascularization procedures [23,24,25]. Despite the use of stent technology or optimal adjunctive medical therapy [26,27], the increased risk occurs in patients with moderate levels of CKD [28]. The mechanisms underlying the unfavorable outcome were not clearly elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the presence of CKD is an independent predictor of subsequent CVD events and mortality in patients with a history of myocardial infarction [19,20,21], acute coronary syndromes [22] and revascularization procedures [23,24,25]. Despite the use of stent technology or optimal adjunctive medical therapy [26,27], the increased risk occurs in patients with moderate levels of CKD [28]. The mechanisms underlying the unfavorable outcome were not clearly elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we found a correlation between ingestion of antiplatelet agents and BB, and the need for readmission. Compliant individual less frequently experienced hospitalization compared to patients indifferent to pharmacotherapy, hence we assume that pharmacological interventions help improve patients' outcome and reduce costs for the healthcare system [21][22][23][24][25][26]. Although our study failed to demonstrate a statistically significant link between patients' clinical features and drug compliance, we managed to denote considerable prevalence of the issue of therapeutic non-adherence and its clinical implications.…”
Section: Discussionmentioning
confidence: 42%
“…Во всех, кроме одного, исследованиях статины назначались при стабильной стенокардии. По данным многоцентрового регистра, включившего 3 227 больных, назначение статинов в течение года после ЧКВ приводило к снижению риска смертельных исходов на 42% (ОР 0,58; 95% ДИ 0,36-0,93; р = 0,02), КШ -на 51% (0,49; 95% ДИ 0,24-1,00; р = 0,05), повторной реваскуляризации -на 26% (0,74; 95% ДИ 0,56-1,00; р = 0,05) [9].…”
Section: статины и эндоваскулярная реваскуляризация миокардаunclassified